Efficacy and Safety of Veno-Arterial Extracorporeal Membrane Oxygenation in the Treatment of High-Risk Pulmonary Embolism: A Retrospective Cohort Study - Tsai, Hao-Yu; Wang, Yu-Tang; Lee, Wei-Chieh; Yen, Hsu-Ting; Lo, Chien-Ming; Wu, Chia-Chen; Huang, Kwan-Ru; Chen, Yin-Chia; Sheu, Jiunn-Jye; Chen, Yen-Yu (Frontiers in Cardiovascular Medicine, 2022)
Objectives: Veno-arterial extracorporeal membrane oxygenation (ECMO) is increasingly used to treat high-risk pulmonary embolism (PE). However, its efficacy and safety remain uncertain. This retrospective cohort study aimed to determine whether ECMO could improve the clinical outcomes of patients with high-risk PE. Methods: Forty patients with high-risk PE, who were admitted to Kaohsiung Chang Gung Memorial Hospital between January 2012 and December 2019, were included in this study. Demographic data and clinical outcomes were compared between patients treated without ECMO (non-ECMO group) and those treated with ECMO (ECMO group). Appropriate statistical tools were used to compare variables between groups and the survival was analysed using the Kaplan–Meier method. Results: The overall in-hospital mortality rate was 55%, in which 65% (26/40) of patients presented with cardiac arrest with a mortality rate of 77%, which was higher than that of patients without cardiac arrest (14%). There was no significant difference in major complications and in-hospital mortality between the non-ECMO and ECMO groups. However, in subgroup analysis, compared with patients treated without ECMO, earlier ECMO treatment was associated with a reduced risk of cardiac arrest (P = 0.023) and lower in-hospital mortality (P = 0.036). A log-rank test showed a significantly higher cumulative overall survival in the earlier ECMO treatment group (P = 0.033). Conclusions: In this retrospective cohort study, earlier ECMO treatment was associated with lower in-hospital mortality among unstable patients without cardiac arrest. Our findings suggest that ECMO can be considered as an initial treatment option for patients with high-risk PE in higher-volume hospitals.